Syntheses of Aristotelia Alkaloids: Reflections in the Chiral Pool - Argade, Malaika D.; Riley, Andrew P. (Synlett, 2022)
The Aristotelia alkaloids are a family of monoterpene indole alkaloids possessing a characteristic azabicyclononane scaffold, which has been assembled by several synthetic methods. Herein we review those approaches that have adopted a biomimetic approach to unite heterocyclic synthons with chiral-pool monoterpenes. Throughout this discussion, the tendency of monoterpenes like α-pinene and limonene to undergo racemization is highlighted, revealing the challenges in developing stereospecific syntheses of these alkaloids. Finally, we provide a brief discussion of how these synthetic efforts have enabled the structural confirmation and elucidation of the Aristotelia alkaloids’ absolute configurations, including our own recent efforts to employ bioactivity data to deduce the naturally occurring configuration of the quinoline alkaloid aristoquinoline.1 Introduction2 Mercury-Mediated Ritter-Like Reactions3 Brønsted Acid Mediated Ritter-Like Reactions4 Synthesis of Aristoquinoline: Ritter-Like Reaction Approach5 Aza-Prins-Type Reaction in the Synthesis of Aristotelia Alkaloids6 Determination of Naturally Occurring Absolute Stereochemistry7 Conclusions
Keywords: alkaloids; chiral pool; Ritter reaction; aza-Prins reaction; biomimetic synthesis